The synthesis of biodiesel from palm oil and waste cooking oil via electrolysis by various electrodes - Darwin; Muhammad Thifal; Muhammad Alwi; Zhairi Murizal; Atmadian Pratama; Muhammad Rizal (Case Studies in Chemical and Environmental Engineering, 2023)
The influence of various electrodes used in the synthesis of biodiesel from palm oil and waste cooking oil via electrolysis processes was studied. The results revealed that electro-catalysts introduced to the transesterification of palm oil and waste cooking oil had significantly enhanced their biodiesel yields. The use of graphite electrode in the transesterification of waste cooking oil via electrolysis could generate the yield of biodiesel was about 87 % while the production of biodiesel from palm oil using platinum electrode could have biodiesel yield about 90 %. The use of electro-catalysts to the transesterification of waste cooking oil and/or palm oil may produce biodiesel with low acid number (0.2–0.4 mg KOH/g), which was lower than that of the ASTM standard. The utilization of electro-catalysts to the transesterification of waste cooking oil and palm oil could lower the ash content of the produced biodiesel (0.0015–0.002 %), which was lower than that of the standard of biodiesel established by ASTM (0.01 %). The process of transesterification of palm oil and waste cooking oil via electrolysis could also generate biodiesel with low viscosity (<5 mm2/s), which met the ASTM and European standards.